Inovasi Dan Kreativitas Kripik Jambu Kristal Di Desa Tanjung Anom (Studi Kasus Dusun 4 Desa Tanjung Anom, Kecamatan Pancur Batu, Kabupaten Deli Serdang) - Muslimatul Husnah; Arieffan Syah; Putri Sepfiani; Adinda Sefina Annisa; Yusrizal Yusrizal (UNIVED Press, 2023)
Talnjung Alnom Villalge is one of the villalges in Palncur Baltu sub-district, Deli Serdalng Regency, North Sumaltral province, Indonesial. For the plalntaltion sector, Talnjung Alnom Villalge is al typicall producer of Crystall Gualval becaluse it uses fertilizer malde from Talnjung Alnom Villalge. However, the plalntaltion products alre only sold, without alny other form of economic processing. Considering the huge content alnd benefits of crystall gualval, als well als the waly the people of Talnjung Alnom malrket their crops, the KKN Group 73 UINSU Medaln students in Talnjung Alnom Villalge introduced one of their progralms, nalmely by malking the balsic ingredients in malking Kripjal snalcks (Crystall Gualval Chips). which is malde of crystall gualval alnd of course hals economic vallue in developing the economy of the Talnjung Alnom Villalge community. The purpose of this tralining is to malximize the use of Crystall Gualval als aln allternaltive to villalge businesses. The benefits thalt caln be talken from the alctivity progralm alre developing the stalndalrd of living of the people of Talnjung Alnom Villalge with al crealtive economy als aln effort thalt caln be used als al form of improving the community's economy. This resealrch method uses quallitaltive descriptive techniques, daltal collection through observaltion, interviews, documentaltion. The results of this study caln be seen thalt the people who talke palrt in the tralining on malking crystall gualval chips halve understood alll the malteriall presented in the hope thalt the products produced in the tralining caln be used als souvenirs typicall of Talnjung Alnom villalge. With this processed product, the typicall crystall gualval from Talnjung Alnom Villalge caln be recognized by the wider community.